Catalytic Wet Air Oxidation of Wastewater Containing Acetic Acid - Tan Yang, Hong (2013)
Wastewater containing acetic acid has long been produced by the chemical industry. Improper disposal of the wastewater has become a major problem as it pollutes the environment and destroys aquatic ecosystem. The wastewater has to be treated before it can be released into the environment. Some of the treatment methods include membrane processes and wet air oxidation (WAO). These treatment methods have a few limitations. Membrane processes are limited by their solvent and thermal stability and WAO is only effective at severe operating conditions. In this research, catalytic wet air oxidation (CWAO) is the proposed method for treatment. The catalyst was synthesized according to the wetness method. The experiment was conducted by oxidizing simulated wastewater containing acetic acid in a batch reactor. The reaction study was repeated with the manipulation of two different operating parameters. The sample was analysed using Total Organic Content (TOC) analysis and Gas Chromatography (GC). The catalyst was characterized by X-ray diffraction (XRD) and Physisorption analysis (BET Method). CWAO yielded the highest conversion at the temperature of 80°C. The catalyst with high surface area was confirmed by XRD and BET. The conversion using CWAO was higher than other processes as predicted. The presence of the catalyst reduced the severity of the operating conditions and also increased the conversion rate.